Surface sterilization and duration of seed storage influenced emergence and seedling quality of African breadfruit (Treculia africana Decne) - Baiyeri, K.P.; Mbah, B. (2006)
The effects of factorial combinations of four storage duration (in days after seed extraction) and surface sterilization with three dilution levels of sodium hypochlorite on seedling emergence and seedling quality of African breadfruit were studied. Storage duration significantly influenced days to seedling emergence, cumulative emergence and seedling quality traits. The effect of sterilization was, however, only significant on deformed seedlings and seedling foliage development. The combined effects of storage duration and sterilization were significant on all traits measured. Seedlings arising from previously sterilized seeds and planted within six days of extraction had fewer cases of deformity and had better foliage development. It was conclusive that after-ripening treatment was necessary to enhance the number of seedling emerging and quality of seedlings of African breadfruit. Sterilizing seeds with 10% dilution of NaOCl and air-drying under ambient tropical room condition for three to six days were found most appropriate, and thus, recommended.